EFL Students’ Perception in Learning English Subject at SMA Negeri 9 Tidore Kepulauan - Nurlaily Sofyan; Rizal Suleman (EDU Journal - English Department of UMMU Journal, 2021)
It is a known fact that English plays a predominant role in the field of education all over the world, and itis used as the common language in the interaction of ELF members who are from diverse cultures and linguistic backgrounds.So, that is why there are many reasons for the student to study English and it is depend on their own perception.The objective of this research is to know the EFL students‟ perception on learning English at SMA Negeri 9 Tidore Kepulauan.This research used qualitative method because it talks about the analysis of EFL students‟ perception on the learning English.Ithas been doneon August 2020. The subject of research is the second grade students of SMA Negeri 9 Tidore Kepulauanlocated in the village of Mafututu, East Tidore district. And, data Analysis employ percentage formula. After present research findings and discussion, the authors drawn the conclusions thatthe EFL students‟ perception on learning English subject is in the good category. The result of this study can be proved by students‟ answer of questionnaire provided shows that the average score from twenty students at SMA Negeri 9 Tidore Kepulauan was 63% which is categorized in the level of good